Penerapan Algoritma Genetika (GA) Pada Penjadwalan Pengamanan Lingkungan - Religian Restu Priharananto; Henki Bayu Seta; Helena Nurramdhani (Fakultas Teknik Universitas Hamzanwadi, 2022)
This research was conducted to facilitate the making of an environmental safety schedule in RT 6. Genetic Algorithm is a discovery algorithm based on the mechanism of biological evolution. Diversity in biological evolution is the variation according to chromosomes between individual organisms. This chromosomal variation will affect the rate of production and the level of the organism's ability to live. The author builds the application scheduling environmental safeguards using genetic algorithms as an alternative to environmental security scheduling that was previously manually converted into an application so that easier and faster. For the initial stage of the research, the authors seek information about the scheduling system which is still manual. The second stage the author makes a scheduling application using the application to make it more efficient effectively and quickly and minimize the occurrence of clashes. In the third stage, the writer collects citizen data to make a schedule of environmental safeguards. To produce an optimal scheduling writer using a genetic algorithm. The fourth stage provides scheduling results from the data that has been collected and selected randomly with an optimal fitness value. The results of this study are: a web-based application that makes it easy for the user so that when making a security schedule, do not use the manual method because it takes 2 hours, while using the application only takes 2 minutes